Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Type the correct answer in each box. Use numerals instead of words. Consider the quadratic equation x2 + 10x + 27 = 0. Completing the square leads to the equivalent equation (x + )2 = .

Sagot :

Answer:

Step-by-step explanation:

ax² + bx + c = y

x² + 10x + 27 = 0

to complete the square, we want the "c" term to be equal to the square of half of the "b" term.

In this case b = 10, half of that is 5. the square of 5 is 25.

We already have c = 27, so to get 25 there we just subtract 2 from each side of the equation.

x² + 10x + 27 - 2 = 0 - 2

x² + 10x + 25 = - 2

         (x + 5)² = - 2

taking the square root of each side

            x + 5 = ±√- 2

the square root of a negative number is an imaginary number

            x + 5 = ±√-1√2

            x + 5 = ± i√2

                  x = - 5 ± i√2